2003
DOI: 10.1002/mde.1103
|View full text |Cite
|
Sign up to set email alerts
|

The causes of mergers: tests based on the gains to acquiring firms' shareholders and the size of premia

Abstract: Despite the large number of event studies of mergers that have been undertaken, considerable disagreement still exists over whether mergers increase the value of the merging firms, and if so why. Most event studies measure the average returns to the acquired and acquiring companies' shareholders separately, and based on these averages conclude either that mergers increase wealth, or that they reduce it. From this the authors go on to claim support either for a hypothesis about how mergers increase efficiency, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 56 publications
1
43
0
1
Order By: Relevance
“…Following this discussion, our 7 The literature reports mixed results regarding the effect of the takeover premia on the abnormal returns gained by acquirers. Hambrick and Hayward (1997) and Mueller and Sirower (2003) find that premia have a negative effect on the acquirers gains. Alexandridis et al (2013) find that the premium estimated using the piecewise regressions, based on the target's stock 52-week high, has a statistically and economically significant negative effect on the acquirers gains.…”
Section: Earnout Financing Takeover Premia and Acquirers' Abnormal mentioning
confidence: 97%
See 2 more Smart Citations
“…Following this discussion, our 7 The literature reports mixed results regarding the effect of the takeover premia on the abnormal returns gained by acquirers. Hambrick and Hayward (1997) and Mueller and Sirower (2003) find that premia have a negative effect on the acquirers gains. Alexandridis et al (2013) find that the premium estimated using the piecewise regressions, based on the target's stock 52-week high, has a statistically and economically significant negative effect on the acquirers gains.…”
Section: Earnout Financing Takeover Premia and Acquirers' Abnormal mentioning
confidence: 97%
“…Primarily, the market's assessment of an increase in the premium can be explained by either: (a) the synergy hypothesis whereby a high premium is interpreted as a reflection of high synergies to be realised from the merger (Antoniou et al, 2008;Díaz et al, 2009) or, (b) the over-investment hypothesis whereby a high premium is interpreted as a signal of managerial discretion and hubris that are leading the acquiring company's board to be engaged in a wasteful acquisition (Mueller and Sirower, 2003;Roll, 1986). 7…”
Section: Earnout Financing Takeover Premia and Acquirers' Abnormal mentioning
confidence: 99%
See 1 more Smart Citation
“…do so in order to lower their costs or generate other efficiencies+ These should create a positive effect on the aggregate profitability of the firms involved in the combination but lower profits for rivals~King, Wilson, & Naseem, 2002!+ Therefore, future research on evaluating M&As in the brewing sector should include the effects of one firm's merger or acquisition on the stock price of its main competitors+ It follows that events affecting one company also affect the other even though the merger has not actually taken place+ Another useful modification would be to assess different modes of M&A transactions~i+e+, friendly versus hostile acquisition, method of payment, domestic versus international, etc+!+ Furthermore, as acquisitions are complicated events, the event windows could be amended through a further step by using a longer window than the common 21-day window~i+e+, Ϫ10, ϩ30 or Ϫ30, ϩ30!+ Because of the complexity of M&As, it takes longer than a few days surrounding the announcement for market participants to correctly determine the extent of the economic implications for the acquiring firm~Baltazar & Santos, 2003;Mueller & Sirower, 2003!+ At the time of announcement, investors will estimate those implications; however, as time passes by and information is released about an acquisition and its performance, investors will revise their initial estimates+ To exemplify this assumption, Carlsberg's acquisition of Holsten should be mentioned+ In the Ϫ10 to ϩ10-window, this deal has indeed seen negative returns but not at a statistically significant level+ In the weeks following the announcement, the shares fell approximately 10%, prompting a clearly negative response from shareholders+ In an event study, review over the last decade, Harrison et al+~2005! found that less than 10% of the event studies published considered returns more than 31 days after the event+ Hence, it is important to consider the relationship between short-term shareholder reactions and long-term outcomes of M&As+ More work on MNCs in the brewing sector could also focus on evaluating the efficiency of various strategies and considering the structural consequences of different internationalization strategies+ Another amendment would be to classify the M&A transactions in the sample according to their specialization or diversification along the geographical lines~Lepetit, Patry, & Rour, 2004!+ For instance, it may be the case that shareholders will react differently to mergers between competitors operating in similar geographical markets than to mergers between companies operating in different geographical markets+ Hence, there are strategic factors that may be used to explain the variation in wealth gains+ This approach is useful to explain why the phenomenon of brewing M&As occurs despite the fact that they do not increase firm value on average+ Finally, it would be particularly helpful in analyzing M&As in the brewing industry to include the target company's abnormal returns+ There is strong empirical evidence in the bulk of event studies to indicate that target firms' shareholders receive significant increases in their stock prices in comparison to the shareholders of bidding firms+…”
Section: Future Researchmentioning
confidence: 93%
“…Mark Sirower and I estimated a mean loss for acquirers' shareholders of -$50.7 million over the two years after the mergers, roughly 2% of the acquirers' pre-merger market values. The standard deviation around this mean was $1,892 million, however -37 times the size of the loss (Mueller and Sirower 2003). Such large standard deviations of returns are common in event studies of mergers, and they raise the question of why managers, who are ostensibly maximizing the wealth of their shareholders, undertake such risky investments with negligible expected returns.…”
Section: Mergersmentioning
confidence: 98%